2019
DOI: 10.1111/cpr.12616
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles exert concentration‐dependent influences on biofilm development and architecture

Abstract: Objectives:To investigate the impact of silver nanoparticles (AgNPs) on the biofilm growth and architecture.Materials and methods: Silver nitrate was reduced by d-maltose to prepare AgNPs in the presence of ammonia and sodium hydroxide. The physicochemical properties of AgNPs were characterized by transmission electron microscopy, ultraviolet-visible spectroscopy and inductively coupled plasma mass spectrometry. The development of biofilm with and without AgNPs was explored by crystal violet stain. The structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“… Guo et al. (2019) observed that subinhibitory doses of AgNPs enhanced polysaccharide and protein production in P. aeruginosa CCM 3955 compared with the control, significantly altering biofilm structure.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“… Guo et al. (2019) observed that subinhibitory doses of AgNPs enhanced polysaccharide and protein production in P. aeruginosa CCM 3955 compared with the control, significantly altering biofilm structure.…”
Section: Discussionmentioning
confidence: 90%
“…Silver nanoparticles (AgNPs) are one of the most widely studied nanomaterials ( Guo et al., 2019 ; Kawish et al., 2020 ; Saeed et al., 2020 ) because of their chemical stability, malleability, flexibility, high electrical and thermal conductivity, catalytic activity, relatively low cost, and, mainly, potent antimicrobial action ( Durán et al., 2019 ). These unique properties have led AgNPs to find application in the medical industry (wound dressing, surgical instrument, and bone prosthesis production), textile industry (garment production), food industry (food packaging, countertop, and cutting board materials), and wastewater treatment ( McNamara and Tofail, 2017 ; Gadkari et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…2) [88,89]. When bacteria is treated with AgNPs, morphological changes are revealed in biofilm's architecture, such as uneven cell surface, suggesting cell lysis [70], relevant morphological damages in the cell wall, membrane corrugation damage, changes in membrane polarization and/or permeability [90], and distinct EPS-matrix formation surrounding the bacterial strains [91]. Moreover, electrostatic interactions between AgNPs and bacterial membranes cause them to rupture, so that AgNPs can penetrate into the mature biofilm [86,92].…”
Section: Antibiofilm Mechanism Of Action Of Agnpsmentioning
confidence: 99%
“…Used as post-treatment therapy, AgNPs were able to reduce P. aeruginosa CCM 3955 biofilm viability by 46.28%, 65.50%, and 92.43% and reduce biomass by 5.69%, 37.87%, and 67.52%, after treatment with concentrations at 2, 6, and 12 μg/mL, respectively [91]. Singh et al [69] evaluated the antibiofilm activity of AgNPs produced from Cannabis sativa against P. aeruginosa PA01 and as a result showed a decrease in biofilm's viability at a concentration at 50 μg/mL.…”
Section: Antibiofilm Activity Of Agnps Against Pseudomonas Aeruginosamentioning
confidence: 99%
“…However, the widespread use of these powerful molecules has led to the apparition of antibiotic-resistant bacterial strains. Silver NPs have broad spectrum activity against gram positive and gram negative bacteria (Agnihotri et al, 2014 ), biofilms (Guo et al, 2019 ), multidrug resistant bacteria (Lara et al, 2010a ), fungi (Kim et al, 2009 ; Chudasama et al, 2011 ), and even some virus (Lara et al, 2010b ). The antibacterial action of silver NPs is dependent on their size and shape (Choi and Hu, 2008 ).…”
Section: Nano-objectsmentioning
confidence: 99%